Rapidly Accumulating Pleural Effusion: A Sequela of Chronic Pancreatitis - Michael Sandhu MD; Michelle Bernshteyn MD; Sanchari Banerjee MD; Michael Kuhn MD (SAGE Publishing, 2022)
Chronic pancreatitis presents with epigastric abdominal pain, nausea, vomiting, and weight loss. Acute pancreatitis can also present with a pleural effusion which is typically left-sided, mild in nature, and self-limiting. However, recurrent bouts of pancreatitis may lead to a pancreaticopleural fistula (PPF) with a large, rapidly recurring, unilateral pleural effusion. Among patients with PPF, the most common presenting complaint is dyspnea. We present the case of a 53-year-old man with recurrent bouts of pancreatitis in the setting of alcohol who presented with progressively worsening shortness of breath. A high-resolution computed topography scan of the thorax demonstrated a large right-sided pleural effusion. A thoracentesis was performed with pleural fluid studies showing an exudative effusion with amylase significantly elevated at 18 382 U/L. An endoscopic retrograde cholangiopancreatography was performed which showed a pancreatic duct leak in the tail of the pancreas. A pancreatic sphincterotomy was performed, and a stent was placed into the ventral pancreatic duct. The patient's shortness of breath improved, and he was discharged home with outpatient follow-up. The aim of this report is to present the diagnosis of a rare complication of chronic pancreatitis and discuss the management and options for treatment.